A corpus-based investigation of explicitation patterns between professional and student interpreters in Chinese-English consecutive interpreting. Issue 4 (2nd October 2017) - Tang, Fang; Li, Dechao
ABSTRACT: This paper investigates the influence of interpreters' expertise on their explicitation patterns in Chinese to English (C-E) consecutive interpreting (CI). An analysis of the performance, notes and retrospection of 12 professional interpreters and 12 student interpreters revealed the following common features: 1) the majority of explicitations are of experiential nature; 2) most explicitations are for clarification; 3) it is common for interpreters to explicitate to make up for competence insufficiency. Additionally, based on differences identified between the two groups, the study revealed the following tendencies: 1) tendency of clarification: professional interpreters tend to clarify the original information; 2) tendency of cohesion enhancement: professional interpreters tend to add conjunctive adjuncts to enhance cohesion; 3) tendency of subjective reinforcement: professionals tend to reinforce the speaker's attitude by adding attitudinal information or intensifiers; 4) tendency to use explicitation as a strategy to make up for inadequate interpreting competency: student interpreters tend to explicitate for time-management and gap-filling purposes. This descriptive study of explicitation based on a self-built corpus of professional and student interpreters' interpreting products may provide insight for interpreter training.